The mummy's curse - Chambers, Catherine, 1954- (London : Dorling Kindersley, 2014)
The members of the time traveling club, SLIP, journey to ancient Egypt to uncover the truth about a mummy's curse.
Includes index.
Keywords: Mummies -- Juvenile literature; Readers (Primary); Readers (Elementary)